Subungual Malignant Melanoma: Difficulty in Diagnosis. Issue 5903 (23rd February 1974) - Leppard, Barbara; Sanderson, K. V.; Behan, F.
Abstract : Subungual malignant melanoma developed on both great toes of a 61-year-old woman. The lesions had been diagnosed elsewhere as ingrowing toenails and had been treated as such for two years. The difficulty in clinical diagnosis is illustrated by the description of three other patients with subungual malignant melanoma. The tumour should be considered as a possible cause of any persistent abnormality of the nail bed or the nail itself, especially if it is pigmented.